Prevalence, extended-spectrum β-lactamase and biofilm production ability ofEscherichia coli isolated from buffalo mastitis - YADAV, SARITA; DEVI, PARVINA; BOORA, ASHOK; NISHU; KUMAR, PRADEEP; AMANDEEP; LOHCHAB, RAJESH KUMAR; KUMAR, ANIL (The Indian Journal of Animal Sciences, 2023)
This study aimed to determine the prevalence, antibiotic resistance pattern, extended-spectrum, beta-lactamase production and biofilm forming ability of isolated E. coli strains from buffaloes mastitis milk. Out of 549 bacterial isolates from mastitis milk of buffaloes (n, animal level= 472) between 2019 and 2022, a total of 43 E. coli strains were isolated with an overall prevalence of 9.11% at animal level. Prevalence of E coli was high in unorganised buffalo herd (11.36%) from villages of Farmer FIRST project (ICAR-FFP) compared with organised buffalo farms (6.73%). The highest resistance was against Penicillin 43 (100%) followed by Ceftriaxone 18 (41.86%), Amoxycillin/Sulbactam 8 (18.60%) and Enrofloxacin 7 (16.27%). Additionally, all were sensitive to gentamycin 43 (100%) followed by Cefoperazone/Sulbactam 34 (79.06%). Cephalosporins are frequently used antibiotics to treat bovine mastitis. However, their therapeutic effectiveness is being compromised by bacterial resistant to β-lactams. In present study, a total of 32 (6.78% %) extended-spectrum β-lactamase (ESBL) producing E coli were isolated from mastitic buffalo milk (n=43/472). In total, 17 (39.5%) isolates were biofilm producers by microtiter-plate method. There was statistically non-significant relationship between biofilm production and antibiotic resistance as well as between ESBL production and biofilm formation in E coli strains. Present study demonstrated a high occurrence of ESBL and biofilm producing E. coli in buffalo mastitis milk, implementing a significant challenge to treat mastitis in buffaloes, necessitates judicious use of antimicrobials and to explore potential therapeutic agents as substitutes for antibiotics to treat bovine mastitis effectively.